Analysis of biomass in young Scots pine stands as a basis for sustainable forest management in Czech lowlands - Jiří NOVÁK; David DUŠEK; Dušan KACÁLEK; Marian SLODIČÁK (Journal of Forest Science, 2017)
Scots pine covers large areas on sandy soils in lowlands of the Czech Republic. These sites can be threatened by non-sustainable biomass removal after clear-cutting. Totally 14 young pine stands at 14-26 years of age were analysed. Particular biomass components were separated, weighed and analysed to investigate their biomass and nutrient contents such as N, P, K, Ca and Mg. Results showed that leaving slash (needles and branches) plus belowground biomass (stumps and coarse roots) on the site represents 51% of calcium, 62% of magnesium, 74% of nitrogen, 67% of phosphorus and 72% of potassium. The total nutrient pools (without fine roots) were 171-377 kg.ha-1 for nitrogen, 34-72 kg.ha-1 for phosphorus, 74-172 kg.ha-1 for potassium, 82-180 kg.ha-1 for calcium and 19-42 kg.ha-1 for magnesium. Needles and live branches are the most important pools of nutrients and the extraction of these parts of biomass can negatively affect the nutrient balance of forest stands on nutrient-poor sites. Stumps with coarse and fine roots also represent a significant pool of nutrients which is left on the studied sites.